2016
DOI: 10.3390/e18090341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fatty Infiltration of the Liver on the Shannon Entropy of Ultrasound Backscattered Signals

Abstract: This study explored the effects of fatty infiltration on the signal uncertainty of ultrasound backscattered echoes from the liver. Standard ultrasound examinations were performed on 107 volunteers. For each participant, raw ultrasound image data of the right lobe of liver were acquired using a clinical scanner equipped with a 3.5-MHz convex transducer. An algorithmic scheme was proposed for ultrasound B-mode and entropy imaging. Fatty liver stage was evaluated using a sonographic scoring system. Entropy values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…This explains why the FD ratio ASQ parameter monotonically decreases with an increase in the degree of hepatic steatosis. Concurrently, the effect of constructive wave interference leads to increases in signal uncertainty and complexity, making the entropy value [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This explains why the FD ratio ASQ parameter monotonically decreases with an increase in the degree of hepatic steatosis. Concurrently, the effect of constructive wave interference leads to increases in signal uncertainty and complexity, making the entropy value [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the acquired ultrasound backscattered signals digitalized by the imaging system belong to discrete signals, the Shannon entropy of a discrete random variable Y with possible values { y 1 , y 2 , …., y n } (i.e., the envelope data points included within the sliding window) was calculated using the following discrete form: where w (∙) represents the function of probability distribution. In this study, the statistical histogram of the data (bins = 200) was used as an alternative w (∙) for estimation [ 31 , 32 ]. To compare the results of entropy with those of ASQ, ultrasound entropy imaging was constructed using the same WSL (6.9 mm) and WOR (50%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger value of Shannon entropy indicates a greater uncertainty, representing that the ultrasound backscattered signals change from regular to random and even complex states [58]. Clinical studies demonstrated that Shannon entropy increases with increasing severity of hepatic steatosis [22,59,60]. Tsui et al [59] investigated ultrasound entropy imaging for assessing hepatic steatosis of 107 patients, using an ultrasonographic scoring system [36] as the reference standard.…”
Section: Ultrasound Entropy Imagingmentioning
confidence: 99%
“…Clinical studies demonstrated that Shannon entropy increases with increasing severity of hepatic steatosis [22,59,60]. Tsui et al [59] investigated ultrasound entropy imaging for assessing hepatic steatosis of 107 patients, using an ultrasonographic scoring system [36] as the reference standard. A correlation r = 0.63 (p < 0.0001) was reported.…”
Section: Ultrasound Entropy Imagingmentioning
confidence: 99%